Agent-based modelling a tool for complexity - Gallegati, M. (Cambridge University Press, 2024)
This Element works as non-technical overview of Agent-Based Modelling (ABM), a methodology which can be applied to economics, as well as fields of natural and social sciences. This Element presents the introductory notions and historical background of ABM, as well as a general overview of the tools and characteristics of this kind of models, with particular focus on more advanced topics like validation and sensitivity analysis. Agent-based simulations are an increasingly popular methodology which fits well with the purpose of studying problems of computational complexity in systems populated by heterogeneous interacting agents.